Manifestation and Management of Cancrum Oris - Mani, Mani M.; Theogaraj, Sam D. (Indian Journal of Plastic Surgery, 1969)
Fifty cases of cancrum oris seen during the past nine years are presented. Exan-thematous fevers—measles, chicken-pox and small-pox occur as the predisposing illness in 48%, of this series.The disease is of acute onset and the gangrene demarcates rapidly.The pattern of tissue necrosis is in the shape of a cone.